TESTING RATIONAL EXPECTATION HYPOTHESIS ON FINANCIAL ANALYSTS EARNINGS FORECAST: A CASE STUDY IN UK - Dinh, Quang (2008)
The main objective of this dissertation is to test rational expectation hypothesis on earnings forecast in United Kingdom market. Ordinary Least Squares (OLS) and Least Absolute Deviation (LAD) are introduced and presented. The study examines the efficiency of the analysts earnings forecast by testing efficiency regarding information variables including past earnings levels and changes, extreme past earnings changes, past returns, past forecast errors and past forecast revisions. Actual and forecasted earning per share (EPS) of 550 selected companies in UK market over the period from 1988 to 2003 is obtained. Three statistical regression and test applied to test the rational expectation include pooled regression and Fama-MacBeth regression and Wald tests which have shown a consistent result of rejecting the efficiency of analysts forecast in the UK market. We also conduct and compare rational expectation tests using OLS and LAD. Least Absolute Deviation is taken into consideration of heteroscedasticity and non-normal distribution, so consistent with previous study we conclude that LAD is more advantageous than OLS regarding to expectation hypothesis tests.